Lithium titanate composite material, preparation method thereof, negative pole piece, lithium battery and electric equipment
The quinoneamine polymer coats lithium titanate to form a porous carbon-coated lithium titanate composite material, which solves the problem of poor conductivity of lithium titanate materials, significantly improves the circulation and rate performance of lithium batteries, and extends the battery life.
Patent Information
- Application Number
- CN202411447135.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-04
AI Technical Summary
The application of lithium titanate materials in lithium-ion batteries is limited by the problems of low specific capacity and poor conductivity, which affects the energy density, safety and cycle life of the battery.
Lithium titanate is coated by initial wet impregnation method using quinoneamine polymer to form a porous carbon-coated lithium titanate composite material, and calcined at high temperature under an argon atmosphere to form a porous channel to improve electrical conductivity.
It significantly improves the conductivity of lithium titanate composite materials, reduces the internal resistance of the electrode plate, improves the circulation and rate performance of lithium batteries, and slows down the attenuation of battery life.
Smart Images

Figure CN119560518A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a lithium titanate composite material and a preparation method thereof, as well as a negative electrode sheet, a lithium battery and electrical equipment. Background Art
[0002] Lithium-ion batteries (LIBs) are highly efficient energy conversion and storage devices that are widely used in electronic products, electric vehicles, space exploration, and other fields. In recent years, in order to meet people's urgent energy needs, improving the energy density, safety, and cycle life of lithium-ion batteries has become the main research direction. As the main component of lithium-ion batteries, negative electrode materials have a huge impact on the performance of batteries. As one of the negative electrode materials for lithium-ion batteries, lithium titanate has the advantages of high safety, high power output, long life, fast charging and discharging, and a wide operating temperature range. However, its shortcomings are also obvious, with low specific capacity and poor conductivity, which directly affect its application in lithium-ion batteries. Therefore, how to modify lithium titanate materials and improve their conductivity has become a hot topic in current research. Summary of the invention
[0003] In view of this, the purpose of the present application is to provide a lithium titanate composite material and a preparation method thereof, so that the lithium titanate composite material can improve its electrical conductivity and the rate performance of the lithium battery and slow down the attenuation of the lithium battery life;
[0004] Another object of the present application is to provide a negative electrode sheet, a lithium-ion battery and an electrical device based on the above-mentioned lithium titanate composite material.
[0005] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, as a first aspect of the present application, a method for preparing a lithium titanate composite material is provided, comprising:
[0006] The lithium titanate is wetted with the quinoneamine polymer solution until the solvent is completely evaporated, and then calcined at high temperature in an argon atmosphere, and then cooled to obtain the lithium titanate composite material.
[0007] Optionally, the quinoneamine polymer is prepared by dripping an amine monomer solution into a quinone monomer solution. Further optionally, the amine monomer includes one or more of phenylenediamine, naphthylamine and phenanthramine, and the quinone monomer includes one or more of benzoquinone, naphthylquinone and phenanthrene.
[0008] Optionally, the high temperature calcination temperature is 750-800°C.
[0009] As a second aspect of the present application, a lithium titanate composite material prepared by the preparation method is provided.
[0010] As a third aspect of the present application, a negative electrode plate is provided, comprising a current collector and a negative electrode active material coated on a surface of the current collector, wherein the negative electrode active material comprises the lithium titanate composite material described in the present application.
[0011] As a fourth aspect of the present application, a lithium battery is provided, comprising a positive electrode plate, the negative electrode plate described in the present application, a separator and an electrolyte.
[0012] As a fifth aspect of the present application, there is provided an electrical device, comprising the lithium-ion battery described in the present application, wherein the lithium-ion battery provides electrical energy for the electrical device.
[0013] This application uses the incipient wetness impregnation method, uses quinone amine polymer to coat the surface of lithium titanate, and forms porous channels after high-temperature sintering to obtain a porous carbon-coated lithium titanate composite material, which not only improves the conductivity of the lithium titanate composite material, reduces the internal resistance of the pole piece, and improves the cycle performance and rate performance of the battery. It also reduces the occurrence of side reactions between lithium titanate and the electrolyte during the battery charge and discharge cycle, slowing down the attenuation of the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Shown is a SEM image of the lithium titanate composite material of the present application;
[0015] Figure 2 Shown are the comparison curves of 55°C and 2C / 2C cycle retention rates of the embodiment and comparative examples 1 and 2;
[0016] Figure 3 Shown is the rate discharge curve of the soft pack battery of Example 1;
[0017] Figure 4 Shown is the rate discharge curve of the soft-pack battery of Comparative Example 1. DETAILED DESCRIPTION
[0018] The present application discloses a lithium titanate composite material and a preparation method thereof, as well as a negative electrode plate, a lithium battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The method described in this application has been described through a preferred embodiment, and relevant personnel can obviously modify or appropriately change and combine the preparation method described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0019] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0020] At present, the carbon sources commonly used in the process of carbon coating lithium titanate are glucose, sucrose, fructose, graphite, conductive carbon black, citric acid, starch, phenolic resin and other substances. However, these conventional carbon sources have poor conductivity, which in turn affects the rate performance and cycle performance of the battery. The present application uses quinoneamine polymer to coat lithium titanate. Compared with other carbon sources, it has certain redox properties and charge transfer properties, is conducive to conductivity, and can improve the rate performance and cycle performance of the battery.
[0021] In the first aspect of the present application, a method for preparing a lithium titanate composite material is provided, wherein the lithium titanate is coated with a quinoneamine polymer by an incipient wetness impregnation method, and the amount of the quinoneamine polymer used can be more accurately controlled, specifically comprising:
[0022] The lithium titanate is wetted with the quinoneamine polymer solution until the solvent is completely evaporated, and then calcined at high temperature in an argon atmosphere, and then cooled to obtain the lithium titanate composite material.
[0023] In certain embodiments of the present application, the quinone amine polymer is prepared by dropping an amine monomer solution into a quinone monomer solution. If the quinone monomer solution is dropped into an amine solution, an excess of amine will result, and the N of the amine reacts with the carbonyl oxygen of the quinone to generate impurities. The mass concentration of the amine monomer solution is 20 to 30 g / L, and the mass concentration of the quinone monomer solution is 20 to 30 g / L.
[0024] In certain embodiments of the present application, the molar ratio of the amine monomer to the quinone monomer is (1.1-1.3):1, for example, 1.1:1, 1.2:1 or 1.3:1.
[0025] In some other embodiments of the present application, the amine monomer includes one or more of phenylenediamine, naphthylamine and phenanthreneamine, wherein the phenylenediamine includes o-phenylenediamine, m-phenylenediamine and p-phenylenediamine. The quinone monomer includes one or more of benzoquinone, naphthylquinone and phenanthrene anthracene, wherein the naphthylquinone includes but is not limited to 1,4-naphthoquinone.
[0026] In certain embodiments of the present application, the amine monomers and quinone monomers are dissolved in one or more solvents selected from ethanol, dimethyl sulfoxide, and dichloromethane to form a solution. After the solvent evaporates, pores may be left behind, providing a basis for subsequent carbon coating of the porous channels.
[0027] In certain embodiments of the present application, the high temperature calcination temperature is 750-800° C., and the high temperature calcination time is 5-6 hours.
[0028] In the second aspect of the present application, a lithium titanate composite material prepared by the preparation method is provided, and its SEM image is shown in Figure 1 The lithium titanate composite material prepared in the present application can reduce agglomeration and increase the specific surface area of the material. In addition, the quinoneamine polymer has good stability and can effectively isolate the electrolyte reaction.
[0029] In the third aspect of the present application, a negative electrode plate is provided, comprising a current collector and a negative electrode active material coated on the surface of the current collector, wherein the negative electrode active material comprises the lithium titanate composite material described in the present application. In certain embodiments of the present application, the negative electrode active material further comprises a binder and a conductive agent, and the mass ratio of the three lithium titanate composite material: binder: conductive agent can be selected as 94:4:2. The conductive agent comprises one or more of a carbon black conductive agent, a carbon nanotube conductive agent, a conductive graphite conductive agent, a graphene conductive agent and a carbon fiber conductive agent. Among them, the carbon black conductive agent comprises conductive carbon black SP, Ketjen black and acetylene black, etc. The binder comprises an aqueous binder and an oily binder, wherein the aqueous binder comprises SBR (styrene butadiene emulsion), CMC (carboxymethyl cellulose), PTFE (polytetrafluoroethylene emulsion), PAA (polyacrylate), and the oily binder comprises PVDF (polyvinylidene fluoride). In certain embodiments of the present application, the current collector comprises a metal foil, such as aluminum foil, copper foil, etc. The lithium titanate composite material, the binder, the conductive agent and the solvent form a negative electrode slurry, which is coated on the surface of the current collector and then dried to volatilize the solvent, thereby obtaining the negative electrode sheet.
[0030] In certain embodiments of the present application, the active material of the positive electrode plate includes a carbon-coated nickel-cobalt-manganese ternary material (NCM), a binder and a conductive agent, and the mass ratio of the three can be selected to be 94:3:3. The preparation process of the positive electrode plate can refer to the preparation process of the negative electrode plate.
[0031] In certain embodiments of the present application, the electrolyte may be a conventional lithium-ion battery electrolyte, typically a LiPF6 electrolyte, such as 1.0M LiPF6, EC / DEC (volume ratio 1:1) and 10% FEC.
[0032] In the fourth aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode plate, a negative electrode plate as described in the present application, a separator and an electrolyte. The lithium-ion battery includes but is not limited to a soft-pack battery, a button battery, a half-cell or a full-cell, etc. In certain embodiments of the present application, a soft-pack lithium battery is provided, in which the positive electrode is coated with the negative electrode, and the positive and negative electrode plates are made into a single cell by a lamination process, and the soft-pack battery is obtained after packaging, liquid injection, and fractionation.
[0033] In a fifth aspect of the present application, an electric device is provided, comprising the lithium-ion battery described in the present application, wherein the lithium-ion battery provides electric energy for the electric device. The electric device may be various devices or equipment driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.
[0034] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0035] The following is a further description of a lithium titanate composite material and a preparation method thereof, as well as a negative electrode sheet, a lithium battery and an electrical device provided in the present application.
[0036] Embodiment 1:
[0037] (1) Measure 100 mL of anhydrous ethanol in a beaker, then weigh 2 g of 1,4-naphthoquinone powder and add it to the ethanol, and stir evenly. Then measure 120 mL of anhydrous ethanol in another beaker, weigh 2.4 g of o-phenylenediamine powder and add it to the ethanol, and stir evenly. Then use a dropper to draw the o-phenylenediamine-ethanol mixed solution and add it dropwise to the 1,4-naphthoquinone-ethanol mixed solution, and continue stirring. After the addition is complete, the system forms a black quinoneamine polymer.
[0038] (2) Take another 1000 mL beaker, weigh 20 g of lithium titanate powder and spread it evenly in it, then use a dropper to slowly drip the quinone amine polymer onto the lithium titanate until the solution just completely wets the powder, forming a quinone amine polymer-coated lithium titanate material.
[0039] (3) The sample was then left to stand until the ethanol evaporated naturally and completely dried, then the sample was transferred to a crucible and calcined at high temperature in a tube furnace. The calcination atmosphere was argon, maintained at 800°C for 6 hours, and the heating rate was 5°C min -1 After the sample is cooled naturally to room temperature, the sample is collected under dry conditions to obtain a porous carbon-coated lithium titanate negative electrode material.
[0040] (4) Preparation of lithium titanate positive electrode sheet: NCM, PVDF, SP and NMP were mixed in a mass ratio of 94:3:3, and a slurry was obtained by stirring. The slurry was coated on the current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain the positive electrode sheet.
[0041] (5) Preparation of lithium titanate negative electrode sheet: The lithium titanate material coated with quinoneamine polymer is mixed with PVDF, SP and NMP in a mass ratio of 94:4:2, and the slurry is obtained by stirring. The slurry is coated on the current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain the negative electrode sheet.
[0042] (6) The positive electrode is coated with the negative electrode to form a single cell by laminating the positive and negative electrode sheets, and then the single cell is packaged, injected with liquid, and divided into different capacities to obtain a soft-pack lithium titanate battery.
[0043] Embodiment 2:
[0044] (1) Measure 100 mL of anhydrous ethanol in a beaker, then weigh 2 g of 1,4-naphthoquinone powder and add it to the ethanol, and stir evenly. Then measure 120 mL of anhydrous ethanol in another beaker, weigh 2.4 g of m-phenylenediamine powder and add it to the ethanol, and stir evenly. Then use a dropper to draw the o-phenylenediamine-ethanol mixed solution and add it dropwise to the 1,4-naphthoquinone-ethanol mixed solution, and continue stirring. After the addition is complete, the system forms a black quinoneamine polymer.
[0045] (2) Take another 1000 mL beaker, weigh 20 g of lithium titanate powder and spread it evenly in it, then use a dropper to slowly drip the quinone amine polymer onto the lithium titanate until the solution just completely wets the powder, forming a quinone amine polymer-coated lithium titanate material.
[0046] (3) The sample was then left to stand until the ethanol evaporated naturally and completely dried, then the sample was transferred to a crucible and calcined at high temperature in a tube furnace. The calcination atmosphere was argon, maintained at 800°C for 6 hours, and the heating rate was 5°C min -1 After the sample is cooled naturally to room temperature, the sample is collected under dry conditions to obtain a porous carbon-coated lithium titanate negative electrode material.
[0047] (4) Preparation of lithium titanate positive electrode sheet: NCM, PVDF, SP and NMP were mixed in a mass ratio of 94:3:3, and a slurry was obtained by stirring. The slurry was coated on the current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain the positive electrode sheet.
[0048] (5) Preparation of lithium titanate negative electrode sheet: The lithium titanate material coated with quinoneamine polymer is mixed with PVDF, SP and NMP in a mass ratio of 94:4:2, and the slurry is obtained by stirring. The slurry is coated on the current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain the negative electrode sheet.
[0049] (6) The positive electrode is coated with the negative electrode to form a single cell by laminating the positive and negative electrode sheets, and then the single cell is packaged, injected with liquid, and divided into different capacities to obtain a soft-pack lithium titanate battery.
[0050] Embodiment 3:
[0051] (1) Measure 100 mL of anhydrous ethanol in a beaker, then weigh 2 g of 1,4-naphthoquinone powder and add it to the ethanol, and stir evenly. Then measure 120 mL of anhydrous ethanol in another beaker, weigh 2.4 g of p-phenylenediamine powder and add it to the ethanol, and stir evenly. Then use a dropper to draw the o-phenylenediamine-ethanol mixed solution and add it dropwise to the 1,4-naphthoquinone-ethanol mixed solution, and continue stirring. After the addition is complete, the system forms a black quinoneamine polymer.
[0052] (2) Take another 1000 mL beaker, weigh 20 g of lithium titanate powder and spread it evenly in it, then use a dropper to slowly drip the quinone amine polymer onto the lithium titanate until the solution just completely wets the powder, forming a quinone amine polymer-coated lithium titanate material.
[0053] (3) The sample was then left to stand until the ethanol evaporated naturally and completely dried, then the sample was transferred to a crucible and calcined at high temperature in a tube furnace. The calcination atmosphere was argon, maintained at 800°C for 6 hours, and the heating rate was 5°C min -1 After the sample is cooled naturally to room temperature, the sample is collected under dry conditions to obtain a porous carbon-coated lithium titanate negative electrode material.
[0054] (4) Preparation of lithium titanate positive electrode sheet: NCM, PVDF, SP and NMP were mixed in a mass ratio of 94:3:3, and a slurry was obtained by stirring. The slurry was coated on the current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain the positive electrode sheet.
[0055] (5) Preparation of lithium titanate negative electrode sheet: The lithium titanate material coated with quinoneamine polymer is mixed with PVDF, SP and NMP in a mass ratio of 94:4:2, and the slurry is obtained by stirring. The slurry is coated on the current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain the negative electrode sheet.
[0056] (6) The positive electrode is coated with the negative electrode to form a single cell by laminating the positive and negative electrode sheets, and then the single cell is packaged, injected with liquid, and divided into different capacities to obtain a soft-pack lithium titanate battery.
[0057] Comparative Example 1:
[0058] (1) Preparation of lithium titanate positive electrode sheet: NCM, PVDF, SP and NMP were mixed in a mass ratio of 94:3:3, and a slurry was obtained by stirring. The slurry was coated on a current collector aluminum foil, and then cold pressed, sheeted, powdered, and selected to obtain a positive electrode sheet.
[0059] (2) Preparation of lithium titanate negative electrode sheet: lithium titanate (without additional treatment) is mixed with PVDF, SP and NMP in a mass ratio of 94:4:2, and a slurry is obtained by stirring. The slurry is coated on a current collector aluminum foil, and then cold pressed, sheeted, powdered and selected to obtain a negative electrode sheet.
[0060] (3) The positive electrode is coated with the negative electrode to form a single cell by laminating the positive and negative electrode sheets, and then the single cell is packaged, injected with liquid, and divided into different capacities to obtain a soft-pack lithium titanate battery.
[0061] Comparative Example 2:
[0062] (1) TiO2 and a conventional carbon source are mixed by dry mixing, and then sintered at 800°C in an argon atmosphere for 3 hours to obtain carbon-coated TiO2; wherein the conventional carbon source is glucose, and the mass of the conventional carbon source is 4.5% of the mass of TiO2.
[0063] (2) After the carbon-coated TiO2 and the lithium source are mixed evenly according to the stoichiometric ratio, the mixture is wet-ground for 5 hours, and the ground material is spray-dried with an inlet temperature of 250°C and an outlet temperature of 60°C. The mixture is sintered at 800°C in an argon atmosphere for 3 hours to obtain carbon-coated lithium titanate.
[0064] (3) Prepare lithium titanate positive electrode sheets by positive method: NCM, PVDF, SP and NMP are mixed in a mass ratio of 94:3:3, and a slurry is obtained by stirring. The slurry is coated on the current collector aluminum foil, and then the positive electrode sheets are obtained by cold pressing, sheet making, powder sweeping and sheet selection.
[0065] (4) Preparation of lithium titanate negative electrode sheet: Carbon-coated lithium titanate (glucose) is mixed with PVDF, SP and NMP in a mass ratio of 94:4:2, and a slurry is obtained by stirring. The slurry is coated on a current collector aluminum foil, and then cold pressed, sheeted, powdered, and selected to obtain a negative electrode sheet.
[0066] (5) The positive electrode is coated with the negative electrode to form a single cell by laminating the positive and negative electrode sheets, and then the single cell is packaged, injected with liquid, and divided into different capacities to obtain a soft-pack lithium titanate battery.
[0067] Experimental example:
[0068] Cycle life test: Charge and discharge the battery at 1C current at room temperature to measure the initial capacity. Stand at 55℃±2℃ for 50min, then charge and discharge at 1C constant current at 55℃±2℃, with an interval of 10min.
[0069] Normal temperature rate discharge capacity test: Each time the battery is charged at room temperature at a 1C rate current, and then discharged from 1C to 12C rate.
[0070] The above electrochemical performance tests were all completed using Titan 5V10A battery test cabinet.
[0071] Depend on Figure 2 It can be seen that the capacity retention rates of Comparative Examples 1 and 2 after 2000 cycles at 55°C and 2C charge and discharge current were 85.07% and 82.19%, respectively, while the capacity retention rates of Examples 1, 2, and 3 under the same conditions were 88.74%, 89.33%, and 89.55%, respectively. The results fully demonstrate that compared with the lithium titanate material without carbon source coating in Comparative Example 1 and the glucose carbon source coated lithium titanate material in Comparative Example 2, the lithium titanate composite material of the present application has better cycle performance.
[0072] Depend on Figure 3 , 4 It can be seen that the 2C rate discharge capacity retention rate of comparative example 1 is 95.75%, and the 12C rate discharge capacity retention rate is 70.96%, while the 2C rate discharge capacity retention rate of Example 1 of the present application is 95.86%, and the 12C rate discharge capacity retention rate is 85.29%. The results show that the lithium titanate composite material of the present application also maintains a significant advantage in rate performance.
[0073] From the above, it can be seen that the conductivity of the lithium titanate material coated with the quinoneamine polymer is improved, making the battery rate performance more excellent. At the same time, during the battery charge and discharge cycle, the side reaction between lithium titanate and the electrolyte is reduced, which slows down the attenuation of the battery life and significantly improves the cycle performance.
[0074] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a lithium titanate composite material, characterized in that: include: The lithium titanate is wetted with the quinoneamine polymer solution until the solvent is completely evaporated, and then calcined at high temperature in an argon atmosphere, and then cooled to obtain the lithium titanate composite material.
2. The preparation method according to claim 1, characterized in that: The quinoneamine polymer is prepared by dropwise adding an amine monomer solution into a quinone monomer solution.
3. The preparation method according to claim 2, characterized in that: The amine monomers include one or more of phenylenediamine, naphthylamine and phenanthrenamine.
4. The preparation method according to claim 2, characterized in that: The quinone monomers include one or more of benzoquinone, naphthoquinone and phenanthrene.
5. The preparation method according to claim 1, characterized in that: The temperature of the high temperature calcination is 750-800°C.
6. The lithium titanate composite material prepared by the preparation method according to any one of claims 1 to 5.
7. A negative electrode plate, characterized in that: It comprises a current collector and a negative electrode active material coated on the surface of the current collector, wherein the negative electrode active material comprises the lithium titanate composite material according to claim 6.
8. A lithium battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet as claimed in claim 7, a separator and an electrolyte.
9. An electrical device, characterized in that: The lithium-ion battery according to claim 8 is included, and the lithium-ion battery provides electrical energy for the electrical equipment.